tìm y : a) 33 × y + 66 × y + y = 400 b) y × 836 + 164 × y = 42000
Tìm y:
a,486:y-126:y=6
b,y×70=42000:60
486 : y - 126 : y = 6
( 486 - 126 ) : y = 6
360 : y = 6
=> y = 360 : 6
y= 60
b, y x 70 = 42000 : 60
y x 70 = 700
y = 700 : 70
y = 10
a)
\(486:y-126:y=6\)
\(\left(486-126\right):y=6\)
\(360:y=6\)
\(y=360:6\)
Vậy \(y=60\)
b)
\(y\times70=42000:60\)
\(y=\frac{42000:60}{70}\)
Vậy \(y=10\)
nha
a , 486 : y - 126 : y = 6
( 486 - 126 ) : y = 6
360 : y = 6
y = 360 : 6
y = 60
b , y \(\times\) 70 = 42000 : 60
y \(\times\) 70 = 700
y = 700 : 70 = 10
cho x:33 dư 5 và y : 66 dư 37. Tìm dư của (x+y) chia hết cho 33
y:66 dư 37 => y = 66k+37=66k+33+4 => y:33 dư 4 mà x:33 dư 5 =>x+y chia 33 dư 9
Tìm y biết
a)y+2,3=15,724
b)127-(y-15)=86
c)2×(y-12)+18=164
a) y+2,3=15,724
=>y =15,724 - 2,3
=>y = 13,424
b) 127-(y-15)=86
=> y-15 = 127-86
=> y-15 = 41
=> y = 41+15
=> y = 56
c) 2 x (y-12)+18 = 164
=> 2 x (y-12) = 146
=> y-12 = 73
=> y = 73 + 12
=> y = 85
a) \(y+2,3=15,724\)
\(y=15,724-2,3\)
\(y=13,424\)
b) \(127-\left(y-15\right)=86\)
\(y-15=127-86\)
\(y-15=41\)
\(y=41+15\)
\(y=56\)
c) \(2\cdot\left(x-12\right)+18=164\)
\(2\cdot\left(x-12\right)=164-18\)
\(2\cdot\left(x-12\right)=146\)
\(x-12=146:2\)
\(x-12=73\)
\(x=73+12\)
\(x=85\)
Câu a) y+2,3=15,724
y=15,724-2,3
y=13,424
Vậy y= 13,424
Câu b) 127-(y-15) = 86
( y-15) = 127-86
y-15= 41
y=41+15
y=56
Vậy y =56
Câu c) \(2\times\left(y-12\right)+18=164\)
\(2\times\left(y-12\right)=164-18\)
\(2\times\left(y-12\right)=146\)
\(y-12=146:2\)
\(y-12=73\)
\(y=73+12\)
\(y=85\)
Vậy
Tìm y biết
a) 127 - ( y - 15 ) = 86
b) 2 x ( y - 12 ) + 18 = 164
\(a,127-\left(y-15\right)=86\)
\(y-15=127-86\)
\(y-15=41\)
\(y=41+15\)
\(y=56\)
\(b,2\times\left(y-12\right)+18=164\)
\(2\times\left(y-12\right)=164-18\)
\(2\times\left(y-12\right)=146\)
\(y-12=146:2\)
\(y-12=73\)
\(y=73+12\)
\(y=85\)
Học tốt
a) 127 - (y - 15) = 86
y - 15 = 127 - 86
y - 15 = 41
y = 41 + 15
y = 56
Vậy y = 56.
b) 2 (y - 12) + 18 = 164
2 (y - 12) = 164 - 18
2 (y - 12) = 146
y - 12 = 146 : 2
y - 12 = 73
y = 73 + 12
y = 85
Vậy y = 85.
127 - ( y - 15 ) = 86
y - 15 = 127 - 86
y - 15 = 41
y = 41 + 15
y = 56
2 x ( y - 12 ) + 18 = 164
2 x ( y - 12 ) = 164 - 18
2 x ( y - 12 ) = 146
y - 12 = 146 : 2
y - 12 = 73
y = 73 + 12
y = 85
Tìm y biết
a) y + 2,3 = 15,7 - 2,4
b) 127 - (y - 15) = 86
c) 2 x (y - 12) + 18 = 164
a)
y + 2,3 = 15,7 - 2,4
y + 2,3 = 13,3
y = 13,3 - 2,3
y = 11
Vậy y = 11
b)
127 - (y - 15) = 86
y - 15 = 127 - 86
y - 15 = 41
y = 41 + 15
y = 56
Vậy y = 56
c)
2 x (y - 12) + 18 = 164
2 x ( y - 12 ) = 164 - 18
2 x ( y - 12 ) = 146
y - 12 = 146 : 2
y - 12 = 73
y = 73 + 12
y = 85
Vậy y = 85
a) y + 2,3 = 15,7 - 2,4
y+2,3=13,3
y=11
b) 127 - (y - 15) = 86
y-15=41
y=56
c) 2 .(y - 12) + 18 = 164
2 .(y - 12) =146
y-12=73
y=85
a) y + 2,3 = 15,7 - 2,4
y + 2,3 = 13,3
y = 13,3 - 2,3
y = 11
Vậy y = 11
b) 127 - (y - 15) = 86
y - 15 = 127 - 86
y - 15 = 41
y = 41 + 15
y = 56
Vậy y = 56
c) 2 x (y - 12) + 18 = 164
2 x ( y - 12) = 164 - 18
2 x ( y - 12 ) = 146
y - 12 = 146 : 2
y - 12 = 73
y = 73 + 12
y = 85
Vậy y = 85
y : 33 = 9/66 4/5 x y = 10/11 : 3/4
1)Tìm y biết
a)18 + 2 x y = 50
b)219 - (y - 19) = 100
c)2 x (y - 12) + 18 = 164
a)18 + 2 x y = 50
2 x y = 50 - 18
2 x y = 32
y = 32 : 2
y = 16
b)219 - (y - 19) = 100
(y - 19) = 219 - 100
(y - 19) = 119
y = 119 - 19
y = 100
c)2 x (y - 12) + 18 = 164
2 x (y - 12) = 164 - 18
2 x (y - 12) = 146
( y - 12 ) = 146 : 2
( y - 12 ) = 73
y = 73 - 12
y = 61
a, 18+2xy=50
2xy=50-18
2xy=32
y=16
b, 219-(y-19)=100
y-19=219-100
y-19=119
y=119+19
y=138
c, 2x(y-12) +18 =164
2x(y-12) =164-18
2x(y-12) =146
y-12 =146: 2
y-12 =73
y =73+12
y = 85
Tìm x,y,z:
a,\(\frac{33}{x}=\frac{45}{120}=\frac{y}{8}=\frac{7}{160}\)
b,\(\frac{55}{66}=\frac{11}{x}=\frac{41}{y}=\frac{7}{12}\)
a)45/120=3/8=y/8->y=3
3/8=33/88->x=88
Cho \(\dfrac{x}{y}=\dfrac{y}{z}=\dfrac{z}{x}\)và x+y+z≠0
Tính A=\(\dfrac{x^{33}.y^{66}}{z^{99}}\)
Theo de bai ta co: \(x=\dfrac{y^2}{z}\Rightarrow\dfrac{z}{x}=\dfrac{z^2}{y^2}\left(1\right)\)
Va \(y=\dfrac{z^2}{x}\left(2\right)\)
Tu (1),(2) suy ra y=z \(\Rightarrow x=y=z\)
suy ra A=1